Bērnu hiperaktivitātes koriģēšanas pedagoģiskie paņēmieni - Medne, Dace (Latvijas Universitāte, 2006)
Maģistra darbs “Bērnu hiperaktivitātes koriģēšanas pedagoģiskie paņēmieni” tika veikts vispārīgās pedagoģijas ietvaros. Pētījuma objekts: bērnu hiperaktivitāte. Pētījuma priekšmets: bērna hiperaktivitātes koriģēšana. Pētījuma mērķis: izpētīt bērnu hiperaktivitāti un izveidot tādu pedagoģisko paņēmienu kopumu, kas veicinātu hiperaktivitātes koriģēšanu. Hipotēze: bērna hiperaktivitātes koriģēšana ir produktīva ja: -katram bērnam individuāli tiek noteikti pedagoģiskie, psiholoģiskie cēloņi uzvedības novirzēm un veikti to koriģējošie pasākumi, -korekcijas procesā aktīvi iesaistās pedagogi, pats hiperaktīvais bērns un viņa vecāki. Lai sasniegtu izvirzīto mērķi un pārbaudītu hipotēzi, maģistra darbam tika izvirzīti šādi uzdevumi: 1.Analizēt hiperaktivitātes cēloņus pedagoģiskajā, medicīniskajā un psiholoģiskajā literatūrā. 2.Apkopot un sistematizēt pedagoģisko paņēmienu kopumu hiperaktivitātes korekcijai. 3.Pārbaudīt sistematizēto paņēmienu kopuma efektivitāti hiperaktivitātes korekcijā. 4.Apkopojot rezultātus, izveidot metodiskās rekomendācijas hiperaktivitātes pedagoģiskā koriģēšanā. Lai sasniegtu pētījuma mērķi, pārbaudītu izvirzīto hipotēzi, maģistra darbā tika izmantotas šādas pētīšanas metodes: 1.Teorētiskās literatūras analīze. 2.Novērošana. 3.Pārrunas. 4.Anketēšana. 5.Statistiskā analīze. Pētījuma bāze Pētījumā piedalījās Rīgas pilsētas un Latvijas rajonu skolu hiperaktīvie sākumskolas skolēni. Skolu nosaukumi ētisku apsvērumu dēļ netiks minēti, jo hiperaktivitāte pagaidām Latvijā ir medicīniska diagnoze.

The Master’s thesis entitled Pedagogical Techniques of Correction of Hyperactivity in Children has been elaborated in the field of general pedagogics. Object of research: hyperactivity of children. Subject of research: correction of hyperactivity of children. Goal or research: to study the hyperactivity of children and create the aggregate of pedagogical techniques, which would contribute to the correction of hyperactivity. Hypothesis: correction of hyperactivity in children is efficient only if: –individually for each child, there are established pedagogical, psychological causes of behavioural deviations and measures are taken to correct the same, –in the process of correction, teachers, the hyperactive child and his parents take an active part. In order to achieve the set goal and to verify the hypothesis of the research, the following tasks have been offered for the Master’s paper: 1.To analyse the reasons of hyperactivity in pedagogical, medical and psychological literature. 2.To summarise and systemise the aggregate of pedagogical techniques in order to correct hyperactivity. 3.To verify the efficiency of the aggregate of systemised techniques for the correction of hyperactivity. 4.Having summarised the results, to create methodical recommendations for the pedagogical correction of hyperactivity. In the course of elaboration of the Master’s paper, the following methods of research have been applied to attain the goal of the research, to verify the hypothesis: 1.Analysis of theoretical sources. 2.Monitoring. 3.The interview. 4.Questionnaires. 5.Statistical analysis. Basis of research: In the research, there participated hyperactive primary school students of Riga and regions of Latvia. For ethical reasons, the name of the schools will not be mentioned, since for now, hyperactivity in Latvia is considered a medical diagnosis. With the change of the scientific paradigm in pedagogics hyperactivity as a phenomenon and as a problem issue is characterized by a principal attitude: to concentrate not only on behaviour, but also to take into consideration the features of the child’s personality. This is a renunciation of linear monocausal (which concerns one cause) thinking, where a chain is formed: reason – symptom – influence – result. Having become an external expression of the problem, hyperactivity points to the disharmony in the social situation of child development, when the model of hyperactive behaviour is necessary for him for the preservation of his/her internal psychic balance.
Educational tools for reducing hyperactivity
Keywords: Pedagoģija